1992
DOI: 10.1159/000258256
|View full text |Cite
|
Sign up to set email alerts
|

Verhaltenstherapie bei Depression im Alter

Abstract: Ausgehend von einer Falldarstellung werden die grundlegenden Merkmale des psychotherapeutischen Arbeitens mit älteren Patienten entwickelt und dargestellt. Diese Prinzipien wirken insbesondere auch auf die verhaltenstherapeutische Arbeit mit depressiven älteren Patienten ein. In dem kurz skizzierten Depressionskonzept werden vor allem die veränderte, eingeschränkte Umwelt, Sozialkontakte, Funktionen und Lebensbedingungen, die angenommene bzw. tatsächliche Nichtkontrolle sowie das Fehlen von Verhaltensalternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The NOSGER total value showed significant differences between the groups of depressive persons with dementia compared to nondepressive persons with dementia, even when the degree of the effect for the interaction of the factors dementia and depression was slight. This may be due to the large area of overlap between these two disorders, making a distinction often difficult (see Hautzinger, 2000). This could also be the reason for a lack of correlation between the degree of dementia and the presence of symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NOSGER total value showed significant differences between the groups of depressive persons with dementia compared to nondepressive persons with dementia, even when the degree of the effect for the interaction of the factors dementia and depression was slight. This may be due to the large area of overlap between these two disorders, making a distinction often difficult (see Hautzinger, 2000). This could also be the reason for a lack of correlation between the degree of dementia and the presence of symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Dementia and depression are among the most frequent psychiatric diseases in old age (Hegerl, Zaudig, & Möller, 2001). However, data on comorbidity of dementia and depression are strikingly heterogeneous and differ widely depending on the study design and method (Hautzinger, 2000;Kales, Chen, Blow, Welsch, & Mellow, 2005). Wetzels, Zuidema, de Jonghe, Verhey, and Koopmans (2010) showed that approximately one fourth of all nursing-home residents with dementia developed symptoms of depression within a period of 2 years.…”
Section: Introductionmentioning
confidence: 99%